2008
DOI: 10.1002/ijc.23750
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive, menstrual, and other hormone‐related factors and risk of renal cell cancer

Abstract: A role of hormone-related factors in renal cell cancer (RCC) etiology has been hypothesized, but the epidemiological evidence is inconsistent. The present study aimed at evaluating the effect of reproductive, menstrual and other gender-specific variables on RCC risk among women. This study is part of a larger hospitalbased, case-control study on RCC risk, conducted in northern, central and southern Italy. Cases were 273 women, below age 80, with histologically confirmed, incident RCC. Controls were 546 women h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
(60 reference statements)
0
44
0
Order By: Relevance
“…In classic epidemiological studies, it was defined that, for women, ccRCC risk was inversely related to age at first given birth (OR=0.7; for ≥25 vs. <25 years), and that hysterectomies doubled ccRCC risk (OR=2.3). A negative association between ccRCC and age at menarche was also shown, suggesting a link between steroid sex hormones and ccRCC (17). Moreover, high parity was shown to be associated with an increased risk of ccRCC, while oral contraceptive use was associated with a reduced risk.…”
Section: Hormone Signaling Pathways As Treatment Targets In Renal Celmentioning
confidence: 83%
“…In classic epidemiological studies, it was defined that, for women, ccRCC risk was inversely related to age at first given birth (OR=0.7; for ≥25 vs. <25 years), and that hysterectomies doubled ccRCC risk (OR=2.3). A negative association between ccRCC and age at menarche was also shown, suggesting a link between steroid sex hormones and ccRCC (17). Moreover, high parity was shown to be associated with an increased risk of ccRCC, while oral contraceptive use was associated with a reduced risk.…”
Section: Hormone Signaling Pathways As Treatment Targets In Renal Celmentioning
confidence: 83%
“…The number of cases enrolled in these studies ranged from 56 (25) to 608 (21), and the number of control subjects varied from 227 (22) to 5,619 (25). Control subjects were drawn from the general population in 5 studies (13,(21)(22)(23)28), hospitals in 3 studies (16,25,26). The highest parity number varied from 3 (16) to more than 6 (21).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four prospective (15,(17)(18)(19)) and 7 case-control studies (13,16,21,22,25,26,28) were included in the doseresponse analysis. The summary relative risk per live birth was 1.08 (95% CI, 1.05-1.10), with none of heterogeneity (Q ¼ 9.34; P ¼ 0.500; I 2 ¼ 0%; Table 2 and Fig.…”
Section: Dose-response Analysismentioning
confidence: 99%
“…Reductions in risk of renal cell cancer have been reported among users of oral contraceptives in some, 76,148 but not all studies, 149,150 and in the large international case-control study protection was restricted to nonsmokers. 76 Several studies have reported an almost two-fold increased risk among women with high parity compared with nulliparous women, after adjustment for obesity, 76,148,151 and an inverse association between age at fi rst birth and risk of renal cell cancer has been reported in some 28,39,149,151 but not all studies.…”
Section: Hormonal and Reproductive Factorsmentioning
confidence: 99%
“…76 Several studies have reported an almost two-fold increased risk among women with high parity compared with nulliparous women, after adjustment for obesity, 76,148,151 and an inverse association between age at fi rst birth and risk of renal cell cancer has been reported in some 28,39,149,151 but not all studies. 148,150 Hormones have induced renal tumors in laboratory animals; however, with the exception of a positive association with parity, evidence for a role of hormonal or reproductive factors in the etiology of renal cell cancer in humans is limited and not entirely consistent to date.…”
Section: Hormonal and Reproductive Factorsmentioning
confidence: 99%